Parental Evaluation of a Responsive Parenting Program for Infants with Hearing Loss - Reinhild Glanemann; Karen Reichmuth; Stephanie Brinkheetker; Antoinette am Zehnhoff-Dinnesen; Katrin Neumann (Children)
Background: Parental satisfaction is an important factor in the evaluation of early intervention programs but is rarely investigated. The Muenster Parental Program (MPP) is a short, evidence-based early intervention program that focuses on parental responsiveness. It is a family-centered intervention for parents of infants aged 3–18 months who have recently been diagnosed with hearing loss and fitted with hearing devices, including prior to or following cochlear implant surgery. Objective: We aim to receive feedback from parents regarding the process and outcomes of their participation in the MPP. Method: Following their participation, all participants of the MPP were asked to complete an evaluation questionnaire. This article reports feedback from the first 52 participants (44 mothers, 7 fathers, and 1 godmother). Their infants (N = 45) had moderate to complete hearing loss, they were aged 2–20 months, and 40% of them had an additional disease, disorder, and/or developmental delay. Results: Parents reported high levels of satisfaction with the content, didactics, setting, and individual benefits of the intervention, and a high recommendation rate (92%). The aspects most appreciated were meeting other affected parents and the concrete individual support of parent–child communication, including video feedback. Almost all parents (96%) reported a change in their communication style with their child. This confirms the results of a previous controlled intervention study on the enhancement of parental responsiveness via the MPP. Conclusions: This evaluation of the MPP from a parental point of view has revealed equally high satisfaction with the content, setting, and didactics amongst all parents regardless of any potentially influential parent or child variables. The MPP is well suited to a wide range of close caregivers’ needs despite the known diversity of children with hearing loss and their parents or families.